Recent highlights on Omicron as a new SARS-COVID-19 variant: evolution, genetic mutation, and future perspectives. (3rd July 2022) - Khairnar, Pooja; Soni, Mukesh; Handa, Mayank; Riadi, Yassine; Kesharwani, Prashant; Shukla, Rahul
Abstract: COVID-19 has affected the lives of billions of people and is a causative agent for millions of deaths. After 23 months of the first reported case of COVID-19, on 25th November 2020, a new SARS-COVID-19 variant, i.e. Omicron was reported with a WHO tagline of VoC that trembled the world with its infectivity rate. This fifth VoC raised the concern about neutralising ability and adequate control of SARS-COVID-19 infection due to mass vaccination drive (nearly more than 4.7 billion individuals got vaccinated globally till December 2021). However, the present scenario of VoCs highlights the importance of vaccination and public health measures that need to be followed strictly to prevent the fatality from Omicron. The world still needs to overcome the hesitancy that poses a major barrier to the implementation of vaccination. This review highlights the SARS-COVID-19 situation and discusses in detail the mutational events that occurred at a cellular level in different variants over time. This article is dedicated to the scientific findings reported during the recent outbreak of 2019–2022 and describes their symptoms, disease, spread, treatment, and preventive action advised. The article also focuses on the treatment options available for Covid-19 and the update of Omicron by expert agencies.